Blaming the victim: assessment, examinations, and the responsibilisation of students and teachers in neo-liberal governance. Issue 1 (2nd January 2017) - Torrance, Harry
ABSTRACT: Historically, for a period of a hundred years or more from the 1860s to the 1960s, assessment developed as an educational technology for selecting and certificating small numbers of individual students. This process was largely focused on excluding the majority. Over the last 30–40 years, the focus and purpose of assessment has changed. The emphasis is now on education for all and the development of a fit-for-purpose assessment system as a system, that is, as part of an integrated approach to national human resource development. These changes have been both driven by, and contributed to, the development of the knowledge economy and neo-liberalism. Students and teachers have been 'responsibilised' for the quality and outcomes of education, with assessment and examinations providing the quintessential vehicle for individualising and responsibilising success and failure in relation to achievement and social mobility.